Critical issues in lean manufacturing programs: A case study in Kurdish iron & steel factories. Issue 1 (1st January 2017) - Hama Kareem, Jamal Ahmed; Mohamad Al Askari, Pirshing Salih; Muhammad, Farooq Hussain
Abstract: The main idea of lean manufacturing is actually simple and means relentlessly work on eliminating waste from the manufacturing process. However, after implementing these systems, many organizations find it difficult to achieve the desired results of them. Thus, the lean manufacturing remains an important area of research. For the importance of what was presented, this paper tries to investigate the critical issues affecting the success of implementing lean manufacturing programs in the iron and steel factories in the Kurdistan Region of Iraq. To achieve this end, the mixed methods represented in a questionnaire survey and semi-structured interviews to collect the data in the framework of the case study were chosen. The questionnaire instrument already has been tested. The results of the study revealed that the importance of management commitment and allocate resources, ethical train the workforce and ethical instructions as the critical success issues of lean implementation. Based on the findings, the organization managements are recommended to provide financial and moral support to employees to enable a successful implementation of lean manufacturing aimed at obtaining the desired results of them.